2021
DOI: 10.1007/s11701-021-01286-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic right hemicolectomy: a case-matched study

Abstract: The current gold standard surgical treatment for right colonic malignancy is the laparoscopic right hemicolectomy (LRH). However, laparoscopic surgery has limitations which can be overcome by robotic surgery. The benefits of robotics for rectal cancer are widely accepted but its use for right hemicolectomy remains controversial. The aim of this study was to compare outcomes in patients undergoing robotic right hemicolectomy (RRH) and LRH in a university teaching hospital. Demographic, perioperative and postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the last year more robot-assisted right colectomy (RAC) has been described highlighting the advantages of the robotic approach due to a three-dimensional and magnified image with a stable camera, the eldest dexterity of instruments and the possibility for the surgeon to independently control the camera 1–8. These advantages improve postoperative outcomes, but the cost still remains a controversial issue that may restrict its application 9. In the previous years several studies have been published comparing RAC with the laparoscopic approach (LA) performing a cost-effectiveness analysis 3 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last year more robot-assisted right colectomy (RAC) has been described highlighting the advantages of the robotic approach due to a three-dimensional and magnified image with a stable camera, the eldest dexterity of instruments and the possibility for the surgeon to independently control the camera 1–8. These advantages improve postoperative outcomes, but the cost still remains a controversial issue that may restrict its application 9. In the previous years several studies have been published comparing RAC with the laparoscopic approach (LA) performing a cost-effectiveness analysis 3 10.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous years several studies have been published comparing RAC with the laparoscopic approach (LA) performing a cost-effectiveness analysis 3 10. The results from the experience published in the literature showed that the robotic approach for the RAC is a feasible and safe procedure compared with LA 9. Furthermore these studies concluded that RAC is well accepted in terms of cost-effectiveness in a healthcare panorama 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the advantages provided include a stable three-dimensional view directly controlled by the operating surgeon, elimination of tremors, improved ergonomics, and 180° articulation with a 540° rotation for a wider range of motion. However, there has been widespread criticism of robotic right hemicolectomy (RRH), including increased cost and longer operation time, as well as the inartificial advantages of robotic platforms being less remarkable in the larger intra-abdominal cavity compared to the pelvis, and impaired ergonomics and range of motion due to instrument collision (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously published a video demonstrating a sutured end-to-end anasto- Laparoscopic right hemicolectomy has become the gold standard approach to right colonic cancers due to benefits including faster recovery and shorter in hospital stay [4]. Further techniques have been reported for the surgical treatment of right colonic cancer including complete mesocolic excision (CME) described by Hoenberger et al [5] and robotic right hemicolectomies [6]. Robotic-assisted surgery has grown in popularity over the years due to the ergonomic advantages over laparoscopic surgery; however, the benefits of right colon cancer surgery remain limited with only a few studies demonstrating improved outcomes [7].…”
mentioning
confidence: 99%